1974
DOI: 10.1073/pnas.71.8.3299
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Action of Cholera Toxin: Stabilization of Catecholamine-Sensitive Adenylate Cyclase in Turkey Erythrocytes

Abstract: Preincubating turkey erythrocytes with cholera toxin alters their adenylate cyclase (EC 4.6.1.1) system: basal activity, maximal epinephrine-stimulatable activity, and affinity of the enzyme reaction for epinephrine are all increased. Pretreatment of erythrocytes with choleragenoid prevents these changes. Cholera toxin does not alter [PHlepinephrine uptake by intact erythrocytes. The increase in epinephrine-stimulatable cyclase activity appears to occur at the expense of fluoridestimulatable activity, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Final points of similarity were obtained by a comparison of the effects of hormones on control and toxin plus NAD-stimulated liver preparations. As reported previously (5), isoproterenol and glucagon both stimulated adenylate cyclase under control and toxin-treated conditions; isoproterenol has been shown to have enhanced activity in toxin-stimulated conditions (5,12); in the study reported here isoproterenol had enhanced activity in the preparation activated by cholera toxin and NAD in vitro. Glucagon stimulated adenylate cyclase in both control and in vitro toxin-treated preparations, as it does in the in vivo toxin-stimulated liver (5).…”
Section: Discussionsupporting
confidence: 60%
“…Final points of similarity were obtained by a comparison of the effects of hormones on control and toxin plus NAD-stimulated liver preparations. As reported previously (5), isoproterenol and glucagon both stimulated adenylate cyclase under control and toxin-treated conditions; isoproterenol has been shown to have enhanced activity in toxin-stimulated conditions (5,12); in the study reported here isoproterenol had enhanced activity in the preparation activated by cholera toxin and NAD in vitro. Glucagon stimulated adenylate cyclase in both control and in vitro toxin-treated preparations, as it does in the in vivo toxin-stimulated liver (5).…”
Section: Discussionsupporting
confidence: 60%
“…Choleragen increases the maximal response of adenylate cyclase of toad erythrocyte plasma membranes to catecholamines, and it increases the apparent affinity of these hormones for activation of the enzyme from rat erythrocyte membranes 1975a). Increased sensitivity of adenylate cyclase activity to catecholamines has also been reported for turkey erythrocytes (Field, 1974), and rat epididymal fat cells (Hewlett et al, 1974). Choleragen also increases the apparent affinity of rat liver adenylate cyclase for activation by glucagon, and it decreases the rate of spontaneous dissociation of 12SI-labeled glucagon from rat liver membranes .…”
mentioning
confidence: 86%
“…While the effect of cholera toxin on adenylate cyclase has been widely studied in a variety of animal tissues (1)(2)(3)(4)(5)(6)(7)(8), the mechanism by which the toxin stimulates the enzyme is not understood. The activation characteristically occurs after a lag period which is variable according to the tissue studied.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously with the increase in basal activity, cholera toxin produces an enhancement of the effects of some hormones on adenylate cyclase. Thus catecholamine responses are enhanced (5,7,8) and the apparent affinity of glucagon for adenylate cyclase is reported to be increased in tissues treated with cholera toxin relative to Received for publication 20 May 1975 and in revised form 26 August 1975. control tissues (6). The ability to respond to fluoride has been shown to be decreased by the toxin treatment (5).…”
Section: Introductionmentioning
confidence: 99%